LITERASI ASURANSI PADA MASA PANDEMI COVID-19 - Darmawan Yudhanegara; Jennifer Mori Villanueva (IKIP SILIWANGI, 2021)
Risks can occur anytime and anywhere due to health insurance, natural disaster losses, business protection, property protection, however, public awareness of the protection given to other parties such as insurance companies is relatively lacking. Many insurance companies take approaches so that people have an interest in insurance, one of which is by holding a teacher volunteer program (TVP) for the first time by the Indonesian General Insurance Association (AAUI) as a literacy program by providing an in-depth understanding of insurance for the community for students and the community. , this program is a literacy stage before the inclusion stage. The method of implementing TVP is carried out by volunteer teachers or teaching staff selected by AAUI which is carried out by each teacher or teaching staff, one of which is through community service in an environment where teachers or teachers can provide insurance literacy in accordance with the goals of TVP in schools or community communities. TVP has succeeded in providing online training, online tests and then providing literacy to the community by 37 teachers and teaching staff throughout Indonesia, both in junior high schools, high schools, and universities. Sekolah Tinggi Teknologi Wastukancana in Purwakarta is one of the places for providing insurance literacy to students through community service programs.